1998
DOI: 10.1016/s0014-5793(98)01057-6
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization and synthesis of a novel pardaxin isoform

Abstract: We report the isolation of a novel pardaxin isoform from the toxic secretion of the Red Sea Moses sole (Pardachirus marmoratus). Mass spectrometrical analysis of the newly purified peptide revealed a different primary structure compared to the previously known pardaxin isoforms. Sequence analysis disclosed an aspartic acid residue instead of glycine at position 31 of the new isoform. According to the novel sequence, a synthetic Asp-31-peptide was compared with the native compound as well as with synthetic Gly-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 24 publications
(30 reference statements)
0
20
0
Order By: Relevance
“…It is known that the membrane protein folding process can be regulated by the membrane parameters such as lipid chain length, fluidity, and head group charge. [30][31][32][33][34][35][36][37][38][39][40] Some studies suggested that the presence of negatively charged lipid in zwitterionic phosphatidylcholine (PC) membrane can induce a higher level of α-helicity of peptide, 41 while other studies claimed the introduction of the anionic phosphatidylglycerol (PG) into the PC vesicles can cause a loss in α-helicity. 42 But the underlying mechanism at the molecular level is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the membrane protein folding process can be regulated by the membrane parameters such as lipid chain length, fluidity, and head group charge. [30][31][32][33][34][35][36][37][38][39][40] Some studies suggested that the presence of negatively charged lipid in zwitterionic phosphatidylcholine (PC) membrane can induce a higher level of α-helicity of peptide, 41 while other studies claimed the introduction of the anionic phosphatidylglycerol (PG) into the PC vesicles can cause a loss in α-helicity. 42 But the underlying mechanism at the molecular level is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Several AMPs have been isolated in teleostean fishes such as misgurin in loach (Misgurnus anguillicaudatus) (Park et al 1997), epinecidin in grouper (Epinephelus coioides) (Yin et al 2005), pleurocidin in winter flounder (P.americanus) (Cole et al 1997), moronecidin in hybrid striped bass (Lauth et al 2002), pardaxin in sole (Pardachirus marmoratus) (Adermann et al 1998), hepcidin in winter flounder (P.americanus), Atlantic salmon (Salmo salar), and perch (P.fluviatilis) (Douglas et al 2003;Rossi et al 2007), parasin in catfish (Parasilurus asotus) (Park et al 1998), and dicentracin in sea bass (D.labrax) (Salerno et al 2007). In fishes, AMPs usually are associated with peripheral blood leucocytes, mucosal surfaces and head kidney, which represents the primary organ involved in immune function (Robert et al 1999;Smith et al 2000;Sarmento et al 2004).…”
Section: Molecular Cloning and Expression Analysis Of Some Genes Invomentioning
confidence: 99%
“…It is believed that the venom has evolved as a defence mechanism used by those flatfishes to repel large predators such as sharks. Five pardaxins have been isolated so far (Adermann et al 1998). They contain 33 amino acids and differ by no more than 3 residues (Fig.…”
Section: Neurotoxins Acting On Lipid Metabolismmentioning
confidence: 99%
“…In neurosecretory cells, pardaxins have been shown to promote both secretion, by stimulating intracellular (Porcelli et al 2004) phospholipase A2, and production of arachidonic acid and eicosanoids (Abu-Raya et al 1998). Arachidonic acid potentiates exocytosis by favouring vesicle fusion competence (Renner et al 1987) and has recently been shown to act directly on the release machinery by stimulating Soluble N-ethylmaleimide sensitive factor attachment protein receptor (SNARE) protein complex production by altering Munc18 function ).…”
Section: Neurotoxins Acting On Lipid Metabolismmentioning
confidence: 99%